1973
DOI: 10.1002/1097-0142(197307)32:1<191::aid-cncr2820320129>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Development and elimination of pigmented moles, and the anatomical distribution of primary malignant melanoma

Abstract: In Sydney, Australia, the number of pigmented moles per person increases to age 15 in males and 20‐29 in females, the most exposed parts of the body reaching peak values soonest. A decline then begins so that moles are almost absent in persons 80 years old. On each part of the body, depigmented spots and nevi with definite or faint halos are more common soon after the peak values have been reached. The delayed development of moles on sunlight‐protected parts of the body may be related to the fact that in Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
42
0
1

Year Published

1992
1992
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(50 citation statements)
references
References 19 publications
7
42
0
1
Order By: Relevance
“…The V126D CDKN2A mutation present in this particular melanoma kindred has a profound effect on nevus development that is exaggerated over a mean follow-up period of 15 y. Individuals carrying this mutation, on average, have increased numbers of nevi, whereas non-carrier and spouse control subjects have decreased numbers of nevi over time in a manner similar to previous population-based studies (Nicholls, 1973;Cooke et al, 1985;MacKie et al, 1985). Moreover, mutation carriers had increased numbers of nevi in all size categories over time, suggesting that these subjects continue to develop new nevi and that existing nevi increase in size with time.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The V126D CDKN2A mutation present in this particular melanoma kindred has a profound effect on nevus development that is exaggerated over a mean follow-up period of 15 y. Individuals carrying this mutation, on average, have increased numbers of nevi, whereas non-carrier and spouse control subjects have decreased numbers of nevi over time in a manner similar to previous population-based studies (Nicholls, 1973;Cooke et al, 1985;MacKie et al, 1985). Moreover, mutation carriers had increased numbers of nevi in all size categories over time, suggesting that these subjects continue to develop new nevi and that existing nevi increase in size with time.…”
Section: Discussionsupporting
confidence: 79%
“…Whereas much is known about the natural history of nevi during the first two decades of life, only a few reports of nevus history in healthy adult populations are available and suggest that: (1) nevi are rare at birth and begin to develop in early childhood (MacKie et al, 1998;Harrison et al, 2000); (2) nevi peak in number at approximately 20-40 nevi during the second through fourth decades of life (Nicholls, 1973;Cooke et al, 1985;MacKie et al, 1985); and (3) nevi decline substantially to very few by the eighth decade (Nicholls, 1973;MacKie et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genesis of .Address correspondence to Ira A. Pion. M.D., 949 Central Avenue, Woodmere, NY 11598. melanocytic nevi (MN) in childhood also .suggests that sun exposure in early life is a factor (8), and the number of MN is directly correlated with the risk of MM (9.10). Consequently, children are a prime target group for education ahout the sun.…”
mentioning
confidence: 93%
“…In adults, there have been no formal studies looking at the difference in naevus phenotype in countries with different exposure patterns. Based on naevus count studies, there is no evidence of a relationship between mean numbers of naevi per individual and melanoma incidence in different countries: naevus-counting studies in healthy individuals in Australia (Nicholls, 1973), New Zealand (Cooke et al, 1985) and the USA have not shown major differences in mean naevus count from those carried out in the UK (MacKie et al, 1985) and Switzerland (Sigg and Peloni 1989). However, these studies have involved different examiners and different naevus-counting protocols, and the results are difficult to compare.…”
mentioning
confidence: 99%